Learning from Nature: Constructing a Smart Bionic Structure for High‐Performance Glucose Sensing in Human Serums. (3rd October 2021) - Tian, Wenyan; Wan, Caichao; Yong, Ken‐Tye; Liu, Sulai; Wei, Song; Zhang, Chonghao; Liu, Xinyi; Su, Jiahui; Cheng, Wenjie; Wu, Yiqiang
Abstract: Traditional noble metal‐based catalysts for glucose sensing usually suffer from easy deactivation by halides and weak sensing properties. To unravel these limits, herein, a novel nature‐inspired design concept (mimicking a "rock–soil–grass" geotexture system) is purposed to build a free‐standing hierarchical micro‐nano architecture. Thanks to the design (rigid and conductive Ni foam) ("rock", underlayer, rough and highly disordered graphene nanosheets (GNSs) ("soil", middle‐layer), and strong catalytic activity of multiscale grass‐like Co3 O4 ("grass", top‐layer), the bionic structure achieves ultra‐high sensitivity, a low limit of detection (120 × 10 −9 m ), an extremely short response time, broad linear ranges (two stages: 1–10 000 and 10 000–30 040 µm ), good anti‐Cl − ‐poisoning and anti‐interference properties, and long‐term stability. Besides the structural design, the "gotong‐royong" effects (the strong interface coupling and charge transfer between GNSs and Co3 O4 and energetically favorable glucose adsorption on Co3 O4 ) also contribute to the high sensing properties, as verified by kinetic studies and density functional theory simulation. To determine human blood glucose levels, the self‐made glucometer with the self‐developed software demonstrates an ultra‐high recovery rate (99.0–100.9%), validating the potential for high‐performance blood‐glucose sensing. Abstract : A novel nature‐inspired design concept (mimicking a "rock–soil–grass" geotexture system) is purposed to build a free‐standing hierarchical micro‐nano architecture. Thanks to the design and "gotong‐royong" effects, the bionic structure achieves a superb glucose sensing property and stability. The self‐made glucometer with the self‐developed software demonstrates an ultra‐high recovery rate, validating the potential for high‐performance blood‐glucose sensing.